PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT LUAHAGUNDRE MANIAMOLO - Hulu, Melfasintia (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
The purpose of this study was to ascertain how leadership style and organizational culture affected worker performance at the Luahagundre Maniamolo District Head Office. This study used multiple linear regression analysis with the equation Y= -8.503+0.388X1+0.8745X2 as the basis for quantitative, causal research. The sample of 30 respondents who worked at the Luahagundre Maniamolo Subdistrict Office comprised the population of this research. The calculated_value (2.670)>t_table (1.703) and the significance level is 0.013<0.05, according to the partial hypothesis testing results. This means that H_a is accepted and H_0 is rejected, indicating that employee performance (Y) is positively and significantly impacted by the organizational culture variable (X1). Simultaneous hypothesis testing findings indicate that the employee performance variable (Y) has a positive and significant influence from the variables Organizational Culture (X1) and Leadership (X2), with a value of F_count (173,696) > F_table (3.354). The study's conclusion is that organizational culture and leadership are the key components in producing high-quality work. The author suggests that in order to enhance employee performance, leaders should be better able to actively participate in all activities and group projects and instill organizational culture in their workforce. This will ensure that all work is carried out in accordance with applicable laws.